Risk Analysis in Halal Supply Chain Management Activities on Aceh Noodle Products (Case Study: Mie Aceh Razali) - Sari, Mutia; Sugianto, Sugianto; Nasution, Muhammad Lathief Ilhamy (Universitas Alma Ata, 2023)
Along with the development of the world's Muslims, the demand for the world halal market has also increased significantly. However, the halal market that is presented sometimes when viewed from the halal management supply chain is vulnerable to the risk of contamination. This research is qualitative research with a descriptive method that aims to see how the management of the halal supply chain through the critical point of halal food in one of the Mie Aceh UMKM. The data obtained is primary data obtained directly from the Aceh Noodle MSME owners, aceh noodle suppliers, seasoning suppliers, and meat suppliers, as well as secondary data obtained from literature or website studies to see that the halal certificate presented on the packaging label is true. The results of the study indicate that the emphasis on halal supply chain management at the research site should be emphasized, because several halal criticalities are obtained, namely through the materials used in the production process so that they are still prone to contamination risks.